Comparison of the concentration of the transforming growth factor Beta 1 (TGF-β1) in synovial fluid of dogs with and without degenerative joint disease - Fischer Wiethuchter, Christof (2018)
Degenerative joint disease (DJD) is a non-inflammatory pathology and characterized to be progressive, structural, and functional. The transforming growth factor Beta 1 (TGF-β1) is a regulatory cytokine participating in the production and deposition of extracellular matrix in various tissues, including joint cartilage. The aim of the present study was to compare the concentrations of transforming growth factor β1 in canine synovial fluid with (n=12) and without DJD (n=11), determined by an ELISA test. The mean concentration of TGB-β1 in dogs without DJD was 16.8 ± 7.1 ng/ml, while in dogs with DJD it was 10.3 ± 3.5 ng/ml (p <0.05).